The Road to Better Assessment: Unleashing the Potential of Feedback Literacy Through Bibliometric Analysis in Education - M.J. Dewiyani Sunarto; Angen Yudho Kisoworo; Julianto Lemantara (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Feedback literacy is a fundamental skill in education that supports academic success, personal growth, and the development of lifelong learning skills. It improves the educational experience by encouraging a culture of improvement and effective communication. Feedback literacy enhances students' learning by leveraging their ability to evaluate feedback. This research analyzes articles on Feedback Literacy using Bibliometric Analysis to explore topic development and research potential. Method: descriptive research that Bibliometric Analysis processes. Results: 106 articles on feedback literacy from 2012 to 2022 were mined from Database Scopus, with the United Kingdom being the leading country contributing to this topic. The most active authors are Paul Sutton and David Carless. The latest trends in feedback literacy are associated with self-assessment, student engagement, socio-material aspects, and interprofessional education. Novelty: The novelty in exploring articles related to feedback literacy is the research associated with individual differences in learning, as each student always desires to be treated differently, especially when receiving feedback and giving feedback to other classmates